Taxonomy of the Palearctic socially parasitic Temnothorax (Myrmoxenus) ants (Hymenoptera: Formicidae). - Ferenc Báthori; Bernhard Seifert; Jürgen Heinze; Kadri Kiran; Celal Karaman; Sándor Csősz (PLoS ONE, 2024)
The ant genus Temnothorax is one of the most diverse in the Palearctic region, comprising several species with different life histories and uncertain taxonomic backgrounds. Socially parasitic Temnothorax ant species were typically described decades ago, primarily based on traditional morphological traits. In some aspects, these species have come back into the spotlight in recent years, necessitating a comprehensive taxonomic revision of the species of the genus. In this paper, we present a quantitative morphology-based taxonomic revision of the Temnothorax corsicus species group (formerly called Myrmoxenus genus) based on the analysis of 20 continuous morphometric traits collected from 394 worker and 19 traits from 473 gyne individuals belonging to 240 samples. Based on morphometric analyses, we propose junior synonymy for Temnothorax tamarae (Arnol'di, 1968) under T. ravouxi (André, 1896), and T. microcellatus (Soudek, 1925) is revived and is considered a senior synonym of T. menozzii (Finzi, 1924). Detailed descriptions, measurements, distribution, and host usage of all ten species are given. Dichotomous keys to workers, known gynes, and photographs of all species are presented.